COMMUNICATIVE COMPETENCE AS A MANDATORY COMPONENT OF THE PROFESSIONALISM OF SOCIAL PEDAGOGUE (World Science, 2019)
The article is devoted to the study of the phenomenon of communicative competence of a social pedagogue. The relevance of the topic of the article is due to the social significance of the issue of the communicative competence formation in the future social pedagogue. The work emphasizes the importance of forming a professional culture of communication among students of higher educational institutions. It is noted that the effectiveness of communicative competence in the work of the future social pedagogue depends on a number of significant components: motives, goals, actions, operations, communication barriers that can change in the process of professional activity. It is noted that the profession of a social pedagogue is distinguished by a variety of functional, role, interpersonal and intergroup relationships. They are complex, ambiguous, closely intertwined, since they cover the social, psychological, moral, economic, legal and many other spheres of life. All this necessitates fluency in the language as a means of communication for future successful professional activities. It is proved that communicative competence is an important component of the professional development of the future social pedagogue and one of the most important components of his professional growth.